PERAN GURU DALAM PROSES PEMBELAJARAN JARAK JAUH - Yofita Gowasa (Jurnal Sabilarrasyad, 2021)
This study aims to determine the role of teachers in the distance learning process. The research method uses library research methods. This discussion is based on expert opinions and the results of previous research on distance learning. The role of the teacher in learning will not be replaced. Technology can improve learning outcomes, but someone still has to keep an eye on the messages in learning. Teachers who can select what is missing and wrong in the process of delivering information. In addition, teachers who know the needs of students by using their approach to solving problems in learning and are able to design learning designs that are in accordance with the problems at hand.